PENGALAMAN DUKUNGAN KELUARGA PADA PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISA: STUDI FENOMENOLOGI DI RUMAH SAKIT IMELDA PEKERJA INDONESIA MEDAN - Ali Sabela Hasibuan; Deddy Sepadha Putra Sagala; Ratna Dewi; Anita Sri Gandria Purba; Juni Mariati Simarmata; Areta Jasa Halawa (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2026)
Hemodialysis is one of the treatments for chronic kidney disease. Because of this condition, it not only causes problems with declining physical health, but also has the potential to cause psychological, social and even spiritual problems, therefore family support from various aspects is one way to overcome this. Family is the closest person who can form interpersonal relationships in attitudes and actions. Therefore, family support has an important influence on chronic kidney disease patients to improve physical, psychological, social and even spiritual health. The purpose of this study was to determine family support for chronic kidney disease patients at the Imelda Buruh Indonesia Hospital, Medan. With qualitative descriptive research through a phenomenological approach. This study was conducted from December 2024 to April 2025. The sampling technique in this study used Purposive Sampling with a total of 8 participants. The research data were collected through interviews and analyzed thematically. The instrument in this study was the researcher himself with interview guideline tools, field notes and recording tools. The results of the study consisted of 4 themes, namely emotional support, information support, instrumental support and appreciation support. The conclusion of this study is that emotional support from the family to the patient is given in the form of the family's willingness to be a companion and provide encouragement and motivation, information support is given in the form of advice and reminders for the patient, instrumental support is given in the form of financing treatment, fulfilling transportation, accompanying and accompanying the patient, while appreciation support is given in theform of assessment and positive encouragement to the patient.